The heterogeneous impact of Brexit: Early indications from the FTSE - Ronald B. Davies; Zuzanna Studnicka (University College Dublin, UCD School of Economics, 2017)
The UK's decision to leave the EU is surrounded by several studies simulating its potential effects. Alternatively, we examine expectations embodied in stock returns using a two-part estimation process. While most firms' prices fell, there was considerable heterogeneity in their relative changes. We show that this heterogeneity can be explained by the firm's global value chain, with heavily European firms doing relatively worse. For firms with few imported intermediates, this was partially offset by a greater Sterling depreciation. These changes were primarily in the first two days and highly persistent. Understanding these movements gives a better understanding Brexit's potential effects.
Keywords: F15; F23; G14; 330; Global Value Chain; Event Study; Brexit